Synthesis of Chromanes and 4H-Chromenes: Exploring the Oxidation of 2H-Chromenes and Dihydro-1-benzoxepines by Hypervalent Iodine(III) - Ahmad, Anees; Silva, Luiz F., Jr. (Synthesis, 2012)
The reaction of various oxygen-containing benzo-fused cycloalkenes were studied with the hypervalent iodine reagent hydroxy(tosyloxy)iodo]benzene [PhI(OH)OTs, HTIB]. 2H-Chromene and 4-methyl-2H-chromene resulted in substituted 4H-chromene and cis-3,4-dialkoxy-4-methyl-3,4-dihydro-2H-chromenes, respectively. Ring contraction to chromanes and benzofurans was observed for dihydrobenzoxepines and 2,2-dimethyl-2H-chromenes, respectively.
Keywords: chromenes; chromanes; Koser’s reagent; ring contraction; hypervalent iodine